High-strength similar high-entropy agglomerated rock ceramic tile and preparation method thereof

By regulating the chemical components and raw material formula of ceramic blanks based on the high entropy model, combined with low temperature fast firing technology, high-entropy granite-like ceramic tiles with high strength were prepared, which solved the limited effect of ceramic tiles in the existing technology and The problem of high cost achieves high strength, low cost and controllable strength.

CN119462106AActive Publication Date: 2025-02-18CHONGQING WONDERFUL CERAMICS CO LTD +2
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411593294.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The prior art has limited effect and high cost when improving the strength of ceramic tiles, making it difficult to meet the needs of mass production.

Method used

By regulating the chemical components and raw material formula of the ceramic body based on the high entropy model, a high entropy state is formed, and combined with low-temperature fast firing technology, high-entropy granite ceramic tiles with high strength are prepared.

Benefits of technology

It achieves high strength improvement of ceramic tiles, has low cost, and controllable and adjustable strength, which is suitable for different usage scenarios and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462106A_ABST
    Figure CN119462106A_ABST
Patent Text Reader

Abstract

The invention provides a high-strength similar high-entropy agglomerated rock ceramic tile and a preparation method thereof, and a ceramic green body of the similar high-entropy agglomerated rock ceramic tile comprises the following chemical components in percentage by weight: 55%-60% of SiO2, 15%-20% of Al2O3, 5%-10% of Fe2O3, 1%-5% of TiO2, 1%-5% of CaO, 0.5%-2% of MgO, 0.5%-5% of K2O and 0.5%-2% of Na2O. According to the embodiment of the invention, the contents of Al2O3, CaO and Fe2O3 are regulated and controlled based on the high-entropy model, and the contents of SiO2 and Al2O3 are maintained in a specific range, so that the phase composition of the agglomerated rock ceramic tile is optimized, a high-entropy state is formed, the strength of the ceramic tile is effectively improved, and the cost is relatively low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic production, and in particular to a high-strength high-entropy granite-like ceramic brick and a preparation method thereof. Background Art

[0002] As is known to all, ceramic materials are brittle materials with lower strength than metal materials and are easily broken by external stress. Therefore, obtaining high-strength ceramic materials to expand the application range of ceramics is the goal pursued in the ceramic field.

[0003] At present, common methods to improve the strength of ceramics include: density enhancement, toughening enhancement, reinforcing phase enhancement and reinforcing layer enhancement. However, the density enhancement method has limited effect on improving strength because the material itself has its limitations. This method requires the use of nanopowders, large-tonnage presses, high-temperature fire protection, etc., resulting in high costs; toughening enhancement requires the introduction of toughening agents, control of microstructures and phase change processes, and the operation is complicated and cannot meet large-scale demand; reinforcing phase enhancement is generally a physical enhancement method, which requires the addition of a certain amount of inorganic fibers to the ceramic material, which increases production costs, and the proportion of added inorganic fibers is limited, and the enhancement effect is also limited. Therefore, the existing methods have limited effects on the enhancement of ceramic tiles and are costly.

[0004] Therefore, the prior art has defects and needs to be improved and developed. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a high-strength high-entropy granite-like ceramic tile and a preparation method thereof in response to the above-mentioned defects of the prior art, aiming to solve the problem that the existing methods for improving the strength of ceramics have limited strengthening effect on ceramic tiles and are relatively costly.

[0006] The technical solution adopted by the present invention to solve the technical problem is as follows:

[0007] In a first aspect, an embodiment of the present application provides a high-entropy granite-like ceramic tile with high strength, wherein the chemical components of the ceramic body of the high-entropy granite-like ceramic tile, measured by weight percentage, include:

[0008] SiO2 55%-60%, Al2O3 15%-20%, Fe2O3 5%-10%, TiO2 1%-5%, CaO1%-5%, MgO 0.5%-2%, K2O 0.5%-5%, Na2O 0.5%-2%.

[0009] According to the above-mentioned technical means, the embodiment of the present application regulates the contents of Al2O3, CaO, and Fe2O3 based on the high entropy model, and maintains the contents of SiO2 and Al2O3 within a specific range, thereby optimizing the phase composition of granite ceramic tiles, forming a high entropy state, and effectively improving the strength of the ceramic tiles at a low cost.

[0010] In one embodiment of the present application, the entropy value of the high-entropy granite-like ceramic tile is within a preset high-entropy range, and the change in the entropy value is obtained by regulating the weight percentage of each chemical component of the ceramic body based on a high-entropy theoretical model.

[0011] According to the above-mentioned technical means, the embodiment of the present application is based on a quasi-high entropy model, and produces granite ceramic tiles of different strengths by adjusting different formulas and application amounts to control the entropy value, thereby achieving the effect of controllable and adjustable product strength, thereby being suitable for different usage scenarios; at the same time, the use of low-temperature fast-firing technology achieves the purpose of reducing production costs while meeting the relevant physical performance requirements.

[0012] In one embodiment of the present application, the raw material formula of the ceramic body comprises, by weight percentage:

[0013] Qingzhen aluminum ore 12%-18%, shale 15%-25%, iron removal slag 25%-35%, Hunan mixed mud 20%-30%, vanadium-titanium slag 3%-12%, tailings 0%-7%.

[0014] According to the above-mentioned technical means, the embodiment of the present application uses industrial waste materials such as iron slag, vanadium-titanium slag as raw materials, and regulates the raw material formula and preparation process through a quasi-high entropy theoretical model to obtain ultra-high strength quasi-high entropy granite ceramic tiles, which can be quickly fired at low temperature, which is energy-saving and environmentally friendly, and can reach three times the national standard modulus of rupture.

[0015] The second aspect of the present application provides a method for preparing the high-entropy granite-like ceramic brick with high strength as described above, which comprises:

[0016] By weight percentage, 12%-18% of Qingzhen aluminum ore, 15%-25% of shale, 25%-35% of iron removal slag, 20%-30% of Hunan mixed mud, 3%-12% of vanadium-titanium slag, and 0%-7% of tailing mud are mixed to obtain a mixed raw material;

[0017] The mixed raw materials are processed to prepare high-entropy granite-like ceramic tiles.

[0018] According to the above-mentioned technical means, the embodiment of the present application uses industrial waste materials such as iron slag, vanadium-titanium slag as raw materials, and regulates the raw material formula and preparation process through a quasi-high entropy theoretical model to obtain ultra-high strength quasi-high entropy granite ceramic bricks, which can be quickly fired at low temperature.

[0019] In one embodiment of the present application, by weight percentage, 12%-18% of Qingzhen aluminum ore, 15%-25% of shale, 25%-35% of iron removal slag, 20%-30% of Hunan mixed mud, 3%-12% of vanadium-titanium slag, and 0%-7% of tailing mud are mixed to obtain the mixed raw material, and the following is further included:

[0020] Determining the weight percentage of each chemical component of the ceramic body based on a high entropy theoretical model so that the high entropy granite-like ceramic brick is in a high entropy state;

[0021] The raw material formula of the ceramic body is determined according to the weight percentage of each chemical component of the ceramic body.

[0022] According to the above technical means, the embodiment of the present application regulates the raw material ratio, particle size distribution, and optimizes the phase composition of ceramic tiles based on the high entropy model to form a high entropy value. This series of adjustments will have a significant impact on the physical properties of ceramic tiles. After the above-mentioned regulation, the fracture modulus of granite ceramic tiles has been greatly improved. This feature enables high-entropy ceramic tiles to have better fracture resistance in practical applications, and can withstand greater external forces without being easily damaged, greatly improving their reliability and durability.

[0023] In one embodiment of the present application, by weight percentage, 12%-18% of Qingzhen aluminum ore, 15%-25% of shale, 25%-35% of iron removal slag, 20%-30% of Hunan mixed mud, 3%-12% of vanadium-titanium slag, and 0%-7% of tailing mud are mixed to obtain the mixed raw material, and the following is further included:

[0024] The Qingzhen aluminum ore is ground and sieved to obtain Qingzhen aluminum ore within a preset particle size range.

[0025] According to the above-mentioned technical means, the embodiment of the present application controls the particle size of the Qingzhen aluminum ore in the raw material by grinding, and makes the particle size distribution of the Qingzhen aluminum ore reach the optimized expectation, thereby increasing the uniformity of raw material mixing and forming a better grain size, so that the matching degree of the raw materials is improved, thereby achieving an increase in the entropy value of the ceramic tile, and then effectively improving the fracture modulus of the granite ceramic tile.

[0026] In one embodiment of the present application, the mixed raw material is processed to prepare a high-entropy granite-like ceramic brick, comprising:

[0027] Adding water, a water reducing agent and a suspending agent to the mixed raw material and then ball milling to obtain a green body slurry;

[0028] De-ironizing and spray-drying the green body slurry to obtain green body powder;

[0029] Pressing the green body powder into a shape and drying it to obtain a dry green brick;

[0030] After the dried brick is glazed and pattern printed, it is fired to obtain a high-entropy granite-like ceramic brick.

[0031] According to the above technical means, the embodiment of the present application can refine the raw materials into tiny particles through ball milling, increase the contact area between particles, and facilitate the reaction and combination in the subsequent process. At the same time, ball milling can also improve the uniformity and stability of the green body slurry. Iron removal can remove iron impurities in the slurry to prevent iron impurities from affecting the color and transparency of ceramic tiles during the firing process; by iron removal, it can be ensured that the ceramic tiles have uniform color and excellent decorative effects. By spray drying, the water in the slurry can be quickly evaporated to obtain green body powder with fine particles and uniform distribution. The purpose of drying after pressing is to remove free water and adsorbed water in the brick blank, improve the strength of the brick blank, and prevent deformation or breakage in subsequent processes. At the same time, drying can also make the brick blank heat up faster during the firing process, shorten the firing cycle, and reduce energy consumption. By glazing, the quality and decorative effect of ceramic tiles can be further improved; through advanced printing technology, various patterns and textures can be accurately printed on ceramic tiles to give them unique decorative effects.

[0032] In one embodiment of the present application, the weight of water added to the mixed raw materials accounts for 38%-42% of the total weight of the raw materials; the weight of the water reducer added to the mixed raw materials accounts for 0.25%-0.35% of the total weight of the raw materials, and the weight of the suspending agent added to the mixed raw materials accounts for 0.15%-0.20% of the total weight of the raw materials; the water reducer is sodium tripolyphosphate, and the suspending agent is sodium methyl cellulose.

[0033] According to the above-mentioned technical means, the embodiment of the present application adds specific proportions of water, sodium tripolyphosphate and sodium methyl cellulose to the mixed raw materials, which can significantly improve the mixing uniformity of the raw materials, optimize the mud performance, improve the production efficiency and improve the performance of the finished product, making the entire production process more efficient, stable and controllable, thereby ensuring the quality and performance of the final product.

[0034] In one embodiment of the present application, the moisture content of the green body powder is 5.0%-7.0% by weight; the strength of the dried brick is 1.8-2.4 MPa.

[0035] According to the above technical means, the embodiment of the present application controls the moisture content to 5.0%-7.0%, so that the green body powder is easier to be compressed and shaped during pressing, thereby obtaining a brick with a regular shape and precise size; too low a moisture content will cause the powder to be too dry and difficult to form; while too high a moisture content will make the powder too viscous, affecting the molding effect. After pressing and forming, the green body powder with a moisture content in the range of 5.0%-7.0% has a tighter combination of particles inside, which is conducive to forming a stronger binding force, so that the dried brick has a higher strength and can withstand greater external forces without being easily broken. In addition, an appropriate moisture content can shorten the drying time, reduce energy consumption, and is less likely to cause problems such as cracks and deformation during the drying process, thereby improving the product yield. If the strength of the dried brick is controlled at 1.8-2.4MPa, its shape and dimensional stability can be better maintained during the subsequent firing process, and the brick with higher strength can better maintain its integrity and aesthetics in subsequent processes such as glazing, printing patterns and firing.

[0036] In one embodiment of the present application, the firing temperature of the high-entropy granite-like ceramic brick is 1185°C-1195°C, and the firing time is 50-55 minutes.

[0037] According to the above-mentioned technical means, after the embodiment of the present application is regulated by a high-entropy theory model, the sintering temperature is reduced from 1300°C to 1185°C-1195°C, and the firing time is shortened from 80-90min to 50-55min, thereby achieving low-temperature fast firing, greatly reducing energy consumption, and still maintaining ultra-high strength.

[0038] Beneficial effects of this application:

[0039] (1) Based on the high entropy model, the contents of Al2O3, CaO, and Fe2O3 are regulated, and the contents of SiO2 and Al2O3 are maintained within a specific range, thereby optimizing the phase composition of granite ceramic tiles and forming a high entropy state, which effectively improves the strength of the ceramic tiles at a low cost.

[0040] (2) Based on a quasi-high entropy model, granite ceramic tiles with different strengths can be produced by adjusting the entropy value through different formulas and application amounts, so that the product strength can be controlled and adjusted, making it suitable for different usage scenarios; at the same time, the use of low-temperature fast-firing technology can achieve the purpose of reducing production costs while meeting the relevant physical performance requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 It is a flow chart of a preferred embodiment of a method for preparing a high-strength high-entropy granite-like ceramic tile in the present invention.

[0042] Figure 2It is a specific flow chart of a method for preparing a high-strength high-entropy granite-like ceramic tile in the present invention. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solution and advantages of the present invention clearer and more specific, the present invention is further described in detail below with reference to the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0044] An embodiment of the present application provides a high-strength high-entropy granite-like ceramic tile. The chemical components of the ceramic body of the high-entropy granite-like ceramic tile, measured by weight percentage, include: SiO2 55%-60%, Al2O3 15%-20%, Fe2O35%-10%, TiO2 1%-5%, CaO 1%-5%, MgO 0.5%-2%, K2O 0.5%-5%, and Na2O 0.5%-2%.

[0045] The embodiment of the present application is regulated based on a high entropy model, that is, by regulating the raw material ratio, particle size distribution, and optimizing the physical composition of ceramic tiles, a high entropy value is formed, thereby improving the physical properties of ceramic tiles.

[0046] The embodiment of the present application regulates the contents of Al2O3, CaO, and Fe2O3 based on the high entropy model, and maintains the contents of SiO2 and Al2O3 within a specific range, thereby optimizing the phase composition of granite ceramic tiles, forming a high entropy state, and effectively improving the strength of the ceramic tiles at a low cost.

[0047] In an embodiment of the present application, the entropy value of the high-entropy granite-like ceramic brick is within a preset high-entropy range, and the change in the entropy value is obtained by regulating the weight percentage of each chemical component of the ceramic body based on a high-entropy theoretical model.

[0048] Specifically, the ceramic tiles of the embodiments of the present application are high-entropy-like ceramic tiles, which are based on the concept of high entropy in materials, and form a high entropy value state in multiphase ceramic tiles to achieve the improvement of specific physical properties. The high entropy theoretical model is a known model. Based on the high entropy theoretical model, the raw material ratio, particle size distribution, and phase composition of ceramic tiles are regulated to form a high entropy value, thereby improving the physical properties of ceramic tiles and increasing their fracture modulus to three times the national standard; at the same time, the introduction of various types of phase structures effectively reduces the sintering temperature and time of granite ceramic tiles, and achieves the purpose of reducing costs and increasing efficiency.

[0049] High entropy ceramic materials have multiple special effects. Under the action of high entropy effect, their structural heterogeneity will be greatly suppressed, showing a single structural phase without the appearance of other structural phases. At the same time, the composition of high entropy materials is complex, and the anions and cations of each component randomly occupy the lattice lattice, which makes it have a higher mixing entropy and improves the structural stability. In addition, the difference in atomic radius size (δ) of each component element also causes huge lattice distortion inside the crystal, and each atom deviates from the equilibrium position, the potential energy increases, the free energy increases, and the effective diffusion rate of atoms in the system is reduced. Finally, the interaction between different components makes its performance present a composite effect, that is, the "cocktail effect" in performance.

[0050]

[0051] Where R is the gas constant, N is the total number of elements, and x i is the atomic fraction of the i-th element. ΔS mix is the entropy of the ceramic mixture.

[0052] The physical properties of ceramic tiles can be regulated by changing the entropy value. Quasi-high entropy ceramics are a complex multiphase structure, and the entropy value is a key parameter for such tiles. That is, the phase composition is used as one of the control variables, and the change of its phase composition can effectively change the entropy value of the material system, thereby greatly improving the physical properties of the ceramics.

[0053] The embodiment of the present application is based on a quasi-high entropy model. By adjusting different formulas and application amounts to control the entropy value, granite ceramic tiles of different strengths are produced, thereby achieving the effect of controllable and adjustable product strength, thereby being suitable for different usage scenarios. At the same time, the use of low-temperature fast-firing technology achieves the purpose of reducing production costs while meeting the relevant physical performance requirements.

[0054] In the embodiment of the present application, the raw material formula of the ceramic body includes, by weight percentage: 12%-18% of Qingzhen aluminum ore, 15%-25% of shale, 25%-35% of iron slag, 20%-30% of Hunan mixed mud, 3%-12% of vanadium-titanium slag, and 0%-7% of tailing mud. Among them, some raw materials (such as Qingzhen aluminum ore) can increase the entropy value by particle size control, which can effectively improve the strength of ceramic tiles. In addition, red gangue can be selected for Hunan mixed mud, and pulping mud can be selected for tailing mud.

[0055] The embodiment of the present application uses industrial waste materials such as iron slag, vanadium-titanium slag, etc. as raw materials, and regulates the raw material formula and preparation process through a quasi-high entropy theoretical model to obtain ultra-high strength quasi-high entropy granite ceramic tiles, which can be quickly fired at low temperature, which is both energy-saving and environmentally friendly, and can reach three times the national standard modulus of rupture.

[0056] The present application also provides a method for preparing the high-entropy granite-like ceramic brick with high strength as described above, such as Figure 1 As shown, the preparation method of the high-strength high-entropy granite-like ceramic brick comprises:

[0057] Step S100, by weight percentage, 12%-18% of Qingzhen aluminum ore, 15%-25% of shale, 25%-35% of iron removal slag, 20%-30% of Hunan mixed mud, 3%-12% of vanadium-titanium slag, and 0%-7% of tailing mud are mixed to obtain a mixed raw material;

[0058] Step S200: Process the mixed raw material to prepare high-entropy granite-like ceramic tiles.

[0059] Specifically, each of the raw mineral materials for the blank is subjected to ball milling and powder making treatment in advance, and the processed raw mineral materials for the blank are blended according to a predetermined blank formulation to obtain a mixed raw material.

[0060] The embodiment of the present application uses industrial waste materials such as iron slag, vanadium-titanium slag, etc. as raw materials, and controls the raw material formula and preparation process through a quasi-high entropy theoretical model to obtain ultra-high strength high-entropy granite-like ceramic tiles that can be quickly fired at low temperature.

[0061] In the embodiment of the present application, before step S100, the following steps are further included:

[0062] Determining the weight percentage of each chemical component of the ceramic body based on a high entropy theoretical model so that the high entropy granite-like ceramic brick is in a high entropy state;

[0063] The raw material formula of the ceramic body is determined according to the weight percentage of each chemical component of the ceramic body.

[0064] The embodiment of the present application regulates the raw material ratio, particle size distribution, and optimizes the physical composition of ceramic tiles based on the high entropy model to form a high entropy value. This series of regulation will have a significant impact on the physical properties of ceramic tiles. Specifically, after the above regulation, the fracture modulus of granite ceramic tiles has been greatly improved. This feature enables high-entropy ceramic tiles to have better fracture resistance in practical applications, and can withstand greater external forces without being easily damaged, greatly improving their reliability and durability.

[0065] In the embodiment of the present application, before step S100, the process further includes: grinding and screening the Qingzhen aluminum ore to obtain Qingzhen aluminum ore within a preset particle size range.

[0066] Specifically, the Qingzhen aluminum ore in the raw materials is ground and screened to adjust the particle size, optimize the particle size distribution of the Qingzhen aluminum ore, increase the uniformity of raw material mixing and form a better grain size, increase the entropy value, and thus improve the fracture modulus of granite ceramic tiles.

[0067] The embodiment of the present application controls the particle size of the Qingzhen aluminum ore in the raw material by grinding, and optimizes the particle size distribution of the Qingzhen aluminum ore to meet expectations, thereby increasing the uniformity of raw material mixing and forming a better grain size, thereby increasing the matching degree of the raw materials, thereby achieving an increase in the entropy value of the ceramic tile, and effectively improving the fracture modulus of the granite ceramic tile.

[0068] In one embodiment of the present application, step S200 specifically includes:

[0069] Adding water, a water reducing agent and a suspending agent to the mixed raw material and then ball milling to obtain a green body slurry;

[0070] De-ironizing and spray-drying the green body slurry to obtain green body powder;

[0071] Pressing the green body powder into a shape and drying it to obtain a dry green brick;

[0072] After the dried brick is glazed and pattern printed, it is fired to obtain a high-entropy granite-like ceramic brick.

[0073] Specifically, adding water to the mixed raw materials can promote the reaction and mixing between the raw materials, so that the raw materials can form a uniform slurry. The water reducer can reduce the amount of water used in the slurry while maintaining the good fluidity of the slurry, reducing the production cost, improving the stability and quality of the slurry, and making the slurry easier to process and operate. Specifically, the water reducer can reduce the viscosity of the slurry and improve its fluidity, thereby meeting the requirements of spraying or filling and leveling. In addition, the water reducer can also reduce the water content of the slurry, prevent the green body from shrinking and deforming and cracking during the drying process, and reduce the breakage rate of the green body. At the same time, the water reducer has a lubricating and grinding-aiding effect on the slurry particles, which can shorten the ball milling time, improve work efficiency, and save energy consumption. The suspending agent helps to maintain the uniform suspension state of the raw material particles in the slurry, prevents the particles from settling and agglomerating, thereby ensuring that the green body slurry obtained after ball milling has a uniform particle distribution and good fluidity.

[0074] The embodiment of the present application can refine the raw materials into tiny particles through ball milling, increase the contact area between particles, and facilitate the reaction and combination in the subsequent process. At the same time, ball milling can also improve the uniformity and stability of the green body slurry. Iron removal can remove iron impurities in the slurry to prevent iron impurities from affecting the color and transparency of ceramic tiles during the firing process; by iron removal, it can be ensured that the ceramic tiles have uniform color and excellent decorative effects. By spray drying, the water in the slurry can be quickly evaporated to obtain green body powder with fine particles and uniform distribution. The purpose of drying after pressing is to remove free water and adsorbed water in the brick blank, improve the strength of the brick blank, and prevent deformation or breakage in the subsequent process. At the same time, drying can also make the brick blank heat up faster during the firing process, shorten the firing cycle, and reduce energy consumption. By glazing, the quality and decorative effect of ceramic tiles can be further improved; through advanced printing technology, various patterns and textures can be accurately printed on ceramic tiles to give them unique decorative effects.

[0075] In an embodiment of the present application, the weight of water added to the mixed raw materials accounts for 38%-42% of the total weight of the raw materials; the weight of the water reducer added to the mixed raw materials accounts for 0.25%-0.35% of the total weight of the raw materials, and the weight of the suspending agent added to the mixed raw materials accounts for 0.15%-0.20% of the total weight of the raw materials; the water reducer is sodium tripolyphosphate, and the suspending agent is sodium methylcellulose.

[0076] Specifically, 42% of water, 0.35% of sodium tripolyphosphate and 0.15% of sodium methylcellulose were added and ball-milled to obtain a green body slurry with a water content of 36.5%.

[0077] In the embodiment of the present application, adding specific proportions of water, sodium tripolyphosphate and sodium methyl cellulose to the mixed raw materials can significantly improve the mixing uniformity of the raw materials, optimize the mud performance, improve the production efficiency and improve the performance of the finished product, making the entire production process more efficient, stable and controllable, thereby ensuring the quality and performance of the final product.

[0078] In the embodiment of the present application, the moisture content of the green body powder is 5.0%-7.0% by weight; the strength of the dried brick is 1.8-2.4 MPa.

[0079] Specifically, the green body slurry is deironed by deironing equipment, spray-dried, and obtained as green body powder with a moisture content of 6.5% by weight. The green body powder is pressed into bricks of required specifications by a press, and dried to obtain dried bricks.

[0080] The embodiment of the present application controls the moisture content to 5.0%-7.0%, so that the green body powder is easier to be compressed and shaped during pressing, thereby obtaining a brick with a regular shape and precise size; too low a moisture content will cause the powder to be too dry and difficult to form; while too high a moisture content will make the powder too viscous, affecting the molding effect. After pressing and forming, the green body powder with a moisture content in the range of 5.0%-7.0% has a tighter combination of particles inside, which is conducive to forming a stronger binding force, so that the dried brick has a higher strength and can withstand greater external forces without being easily broken. In addition, the appropriate moisture content can shorten the drying time, reduce energy consumption, and is less likely to cause problems such as cracks and deformation during the drying process, thereby improving the product yield. If the strength of the dried brick is controlled at 1.8-2.4MPa, its shape and dimensional stability can be better maintained during the subsequent firing process, and the brick with higher strength can better maintain its integrity and aesthetics in the subsequent glazing, pattern printing and firing processes.

[0081] In the embodiment of the present application, the firing temperature of the high-entropy granite-like ceramic brick is 1185°C-1195°C, and the firing time is 50-55min.

[0082] After being regulated by a high-entropy theory-like model, the sintering temperature in the embodiment of the present application is reduced from 1300°C to 1185°C-1195°C, and the firing time is shortened from 80-90min to 50-55min, thereby achieving low-temperature fast firing, greatly reducing energy consumption, and still maintaining ultra-high strength.

[0083] Specifically, due to the introduction of various types of phase structures into ceramic tiles, the sintering process of ceramic tiles has undergone favorable changes, significantly reducing the sintering temperature and sintering time of ceramic tiles. Lower sintering temperature means less energy demand during the production process, while shortening the sintering time can make the production process more efficient. The improvement in these two aspects combined to achieve the optimization goal, and due to the reduction in energy consumption and the improvement in production efficiency during the production process, cost reduction and efficiency improvement have been achieved, thus occupying a more advantageous position in market competition.

[0084] In one embodiment, the density of the high entropy granite-like ceramic tile is as shown in Table 1.

[0085] Table 1

[0086]

[0087]

[0088] From the above test results, it can be seen that based on the quasi-high entropy theory, after adjusting the raw material ratio, the density of the granite ceramic tile after firing shows an upward trend. This phenomenon means that the porosity inside the ceramic tile has decreased to a certain extent, and the bond between the crystal phase material inside it and the green body has become tighter. In the case of formula 3, the density of the granite ceramic tile reached the maximum value, and this maximization of density is conducive to maximizing its modulus of rupture.

[0089] The rupture modulus corresponding to different formulations is shown in Table 2.

[0090] Table 2

[0091]

[0092] The high fracture modulus granite ceramic brick prepared in the embodiment of the present application is based on the quasi-high entropy theory, and the fracture modulus of 105.6 MPa can be achieved by adjusting the raw material ratio and phase composition to form a high entropy state. Therefore, the embodiment of the present application prepares a high fracture modulus granite ceramic brick.

[0093] In one embodiment, Figure 2 As shown, the formula composition is regulated according to the high entropy theory model; the raw materials are selected and mixed according to the proportion; some of the raw materials are pre-milled. The mixed raw materials are ground; the ground raw materials are screened, iron-removed, and spray-dried; pressed into shape to obtain a brick body; the brick body is dried. The kiln is fired quickly at low temperature (1185℃-1195℃, 50-55min); polished and sorted to obtain the finished product.

[0094] The embodiment of the present application optimizes the raw material ratio according to the high entropy theory model, and effectively regulates the physical phase composition inside the granite ceramic tile. This regulation of the physical phase composition is the key to obtaining the high modulus of rupture characteristics. In the production process, the increase or decrease of each raw material affects the internal microstructure of the final granite ceramic tile. When the raw material ratio reaches the ideal state, the physical phase composition inside the ceramic tile is optimized, so that each physical phase cooperates with each other to form a stable and efficient high entropy structure. Finally, the ceramic products produced in this way can reach a modulus of rupture of 105.6MPa, which shows that the granite ceramic tile has an excellent ability to resist fracture when subjected to external force, and can maintain the integrity of the structure under harsh use conditions. The high modulus of rupture granite ceramic tile prepared by the embodiment of the present application has broad application prospects in many fields, whether in architectural decoration, industrial production, or in some special fields with high requirements for material strength, it can play an important role. The comparison of the modulus of rupture and the breaking strength of different product performances is shown in Table 3.

[0095] Table 3

[0096]

[0097] The present invention provides a high-strength high-entropy granite-like ceramic tile and a preparation method thereof. The chemical components of the ceramic body of the high-entropy granite-like ceramic tile include, by weight percentage, SiO2 55%-60%, Al2O3 15%-20%, Fe2O3 5%-10%, TiO2 1%-5%, CaO 1%-5%, MgO 0.5%-2%, K2O 0.5%-5%, and Na2O 0.5%-2%. The embodiment of the present application regulates the contents of Al2O3, CaO, and Fe2O3 based on a high entropy model, and maintains the contents of SiO2 and Al2O3 within a specific range, thereby optimizing the phase composition of the granite ceramic tile, forming a high entropy state, effectively improving the strength of the ceramic tile, and having a low cost.

[0098] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A high-strength high-entropy granite-like ceramic tile, characterized in that: The chemical components of the ceramic body of the high-entropy granite-like ceramic brick, measured by weight percentage, include: SiO2 55%-60%, Al2O3 15%-20%, Fe2O3 5%-10%, TiO2 1%-5%, CaO1%-5%, MgO0.5%-2%, K2O 0.5%-5%, Na2O 0.5%-2%.

2. The high-strength high-entropy granite-like ceramic brick according to claim 1, characterized in that: The entropy value of the high-entropy granite-like ceramic brick is within a preset high-entropy range, and the change in the entropy value is obtained by regulating the weight percentage of each chemical component of the ceramic body based on a high-entropy theoretical model.

3. The high-strength high-entropy granite-like ceramic brick according to claim 1, characterized in that: The raw material formula of the ceramic body includes, by weight percentage: Qingzhen aluminum ore 12%-18%, shale 15%-25%, iron removal slag 25%-35%, Hunan mixed mud 20%-30%, vanadium-titanium slag 3%-12%, tailings 0%-7%.

4. A method for preparing a high-strength high-entropy granite-like ceramic tile according to any one of claims 1 to 3, characterized in that: include: By weight percentage, 12%-18% of Qingzhen aluminum ore, 15%-25% of shale, 25%-35% of iron removal slag, 20%-30% of Hunan mixed mud, 3%-12% of vanadium-titanium slag, and 0%-7% of tailing mud are mixed to obtain a mixed raw material; The mixed raw materials are processed to prepare high-entropy granite-like ceramic tiles.

5. The method for preparing high-strength high-entropy granite-like ceramic tiles according to claim 4, characterized in that: By weight percentage, 12%-18% of Qingzhen aluminum ore, 15%-25% of shale, 25%-35% of iron removal slag, 20%-30% of Hunan mixed mud, 3%-12% of vanadium-titanium slag, and 0%-7% of tailing mud are mixed to obtain the mixed raw material, and the following is further included: Determining the weight percentage of each chemical component of the ceramic body based on a high entropy theoretical model so that the high entropy granite-like ceramic brick is in a high entropy state; The raw material formula of the ceramic body is determined according to the weight percentage of each chemical component of the ceramic body.

6. The method for preparing high-strength high-entropy granite-like ceramic tiles according to claim 4, characterized in that: By weight percentage, 12%-18% of Qingzhen aluminum ore, 15%-25% of shale, 25%-35% of iron removal slag, 20%-30% of Hunan mixed mud, 3%-12% of vanadium-titanium slag, and 0%-7% of tailing mud are mixed to obtain the mixed raw material, and the following is further included: The Qingzhen aluminum ore is ground and sieved to obtain Qingzhen aluminum ore within a preset particle size range.

7. The method for preparing high-strength high-entropy granite-like ceramic tiles according to claim 4, characterized in that: The mixed raw materials are processed to prepare high-entropy granite-like ceramic tiles, including: Adding water, a water reducing agent and a suspending agent to the mixed raw material and then ball milling to obtain a green body slurry; De-ironizing and spray-drying the green body slurry to obtain green body powder; Pressing the green body powder into a shape and drying it to obtain a dry green brick; After the dried brick is glazed and pattern printed, it is fired to obtain a high-entropy granite-like ceramic brick.

8. The method for preparing high-strength high-entropy granite-like ceramic tiles according to claim 7, characterized in that: The weight of water added to the mixed raw materials accounts for 38%-42% of the total weight of the raw materials; the weight of the water reducer added to the mixed raw materials accounts for 0.25%-0.35% of the total weight of the raw materials; the weight of the suspending agent added to the mixed raw materials accounts for 0.15%-0.20% of the total weight of the raw materials; the water reducer is sodium tripolyphosphate, and the suspending agent is sodium methylcellulose.

9. The method for preparing high-strength high-entropy granite-like ceramic tiles according to claim 7, characterized in that: The moisture content of the green body powder is 5.0%-7.0% by weight; the strength of the dried brick is 1.8-2.4MPa.

10. The method for preparing high-strength high-entropy granite-like ceramic tiles according to claim 7, characterized in that: The firing temperature of the high-entropy granite-like ceramic brick is 1185° C.-1195° C., and the firing time is 50-55 minutes.

Citation Information

Patent Citations

  • Environment-friendly full body porcelain brick having characteristic of natural granite, and preparation method thereof

    CN103553579A

  • Marbleized high-strength ceramic brick adobe and production method thereof

    CN107488026A

  • Black ceramic tile with three-dimensional glittering effect and preparation method thereof

    CN114249586A

  • Ceramic tile / plate prepared by dry method and preparation method of ceramic tile / plate

    CN114956799A

  • Low-temperature fast-fired ceramic rock plate and preparation method thereof

    CN115010465A